2021
DOI: 10.1520/gtj20190242
|View full text |Cite
|
Sign up to set email alerts
|

Field Rebound and Recompression Curve of Soft Clay

Abstract: During sampling and sample preparation, the soil specimen is disturbed, which is accompanied by a decrease in void ratio, and the stresses within it release from in situ status to a residual one, usually associated with an expansion to some extent. As a result, the in situ void ratio and field recompression index, i.e., ev0 and CFR, change to e0 and CLR, respectively, which have not been properly accounted for in the traditional method. A rebound-recompression method (RRM) is proposed in this article for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The uniformity of the samples by the static compression method was relatively poor, and there was residual stress during the static pressing, resulting in a lower shear strength of the sample. It is also in accordance with the current research [25,26] that the sample preparation process produces structural differences and residual stresses, and affects its strength.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The uniformity of the samples by the static compression method was relatively poor, and there was residual stress during the static pressing, resulting in a lower shear strength of the sample. It is also in accordance with the current research [25,26] that the sample preparation process produces structural differences and residual stresses, and affects its strength.…”
Section: Discussionsupporting
confidence: 89%
“…After the CU test, the main peak of the pore size of the sample has a significant left shift relative to that before the test, and the pore size distribution shows a good consistency at the main peak. Current studies [25,26] showed that the difference mainly caused by the internal structure of the soil and the internal stresses. In the test, the pore structure significantly changes for the sample prepared by the static compression method, indicating that under the high dry density, the sample is not completely uniform before the test, and there is still a large residual stress inside.…”
Section: Dynamic Triaxial Test Schemementioning
confidence: 99%
“…In this section, based on the previously proposed in-situ rebound-recompression curve [25], we make corrections to the required void ratio and rebound index for the calculation of excavation rebound. By referencing the traditional method for calculating foundation settlement and treating the self-weight stress of the excavated soil as unloading additional stress, we propose a calculation method for excavation rebound based on RRM.…”
Section: The Rebound Calculation Methods Based On Rrm Methodsmentioning
confidence: 99%
“…In reality, soil samples undergo stress relief and disturbance during the collection and preparation process before testing, thereby generating discrepancies between the one-dimensional consolidation compression curve observed in the laboratory and that observed in the field. To address this issue, Li et al [25] proposed a correction method known as the Rebound-recompression method (RRM), which seeks to obtain the in-situ soil parameters for field rebound-recompression curves. The use of RRM enables the utilization of in-situ soil parameters for the calculation of soil rebound resulting from excavation, resulting in more realistic outcomes relative to those generated by laboratory-disturbed soil parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In obtaining the soil sample and preparing it for the laboratory test, soil stress release and disturbance occur simultaneously, resulting in differences between the laboratory compression curves and field compression curves [9,[23][24][25]. To overcome this problem, Li et al [26] proposed a modified approach, the rebound-recompression method (RRM), to obtain the field rebound-recompression curve that can reflect the actual situation more accurately.…”
Section: Introductionmentioning
confidence: 99%